Enhancing participatory governance in biosphere reserves through co-creation of transdisciplinary and intergenerational knowledge - Leguia-Cruz, Marcelo; Cerda, Claudia; Ortiz-Cubillos, Natalia; Mansilla-Quiñones, Pablo; Moreira-Muñoz, Andrés (Frontiers in Environmental Science, 2024)
In the context of the current global climate and biodiversity crisis, urgent action is needed to improve participatory and co-productive governance in territories under sustainability directives, such as Biosphere Reserves. These territories comprise a global network with the potential to apply and replicate sustainability actions, improve livelihoods and boost climate change resilience while reducing impacts on the environment and the biodiversity in all continents. In the Biosphere Reserves network's 50 years of existence, progress and setbacks have been reported in different regions around the world, and there is an urgent need to envision alternative futures. In this contribution we describe the results and reflections of our 'Open Academy' that enhanced the participatory governance in La Campana-Peñuelas Biosphere Reserve in Central Chile. We crossed the traditional assessment with the principles of transdisciplinary and intergenerational knowledge co-creation. Results show that the traditional performance assessment shows a generally poor performance, and reveals the weaknesses of the governance system of the reserve's management.The extraction of water by the mining and agroindustry, uncontrolled urbanization, wildfires, weak social participation and low integration of indigenous communities are crucial issues for the performance of Biosphere Reserves. On the other side, these territories have the potential as models towards post-extractive economies. Enhancing participatory governance, Biosphere Reserves shall serve as: a) agents for configuring the future as an eco-social pact with the territory; b) pilot test areas for alternative futures; and c) places to promote the social collective as a conscious agent of the future.